The relationship between empowerment and employee performance at Pasdec Holdings Berhad / Nurul Hidayah Abdullah - Abdullah, Nurul Hidayah (2017)
This study seeks to examine the relationship between empowerment and employee performance. The research objectives were to identify the empowerment factor that has been practiced among employees and to identify whether is there any relationship between empowerment and employee performance at Pasdec Holdings Berhad (PASDEC). The research method based on correlational research under study was 148 staffs. Empowerment factors, serving others, monitoring others, mentoring others and coaching others were adopted from Mehrabani and Shajari (2013). Hence, employee performance dimensions, performance through work itself, executing defined duties and achieving departmental goals were adopted from Iqbal et al. (2015). However, employee performance dimensions only used to construct the question of the questionnaire. This study applied stratified random sampling. A questionnaire was used and respondents were drawn from 103 employees in Pasdec Holdings Berhad. Eighteen (18) questions of empowerment were adopted from Mehrabani and Shajari (2013), while questions on employee performance were adapted from several study which Achievement Goals (2015) and Dicktam (2015). The questionnaire consists five point Likert Scale question on the section empowerment and employee performance. Statistical Package for Social Science (SPSS) version 20.0 was used to analyze the data. Descriptive statistic based on frequency tables and charts were used to analyze information on demographic profile while descriptive tables and charts were used in section empowerment and employee performance. The tools validity on empowerment and employee performance by Cronbach’s Alpha model with 0.917, 0.803 has been confirmed in actual study. Five (5) hypotheses were developed and tested using Pearson Correlation Coefficient. The results indicates that the empowerment had moderate, positive relationship to the employee performance with value (r=.578, n=103, p<.01). As for conclusion, empowerment had moderate, positive relationship to the employee performance with value (r=.578, n=103, p<.01). As proven in the previous studies there were positive effect of empowerment on employee performance (Kirkman and Rosen, 1999; Spreitzer, 1995; Spreitzer et al., 1997) as cited by Mehrabani and Shajari (2013). Hence, empowerment factors that have been practiced on employee performance at Pasdec Holdings Berhad were coaching others, mentoring others, serving others and monitoring others. This outcomes were identified according to the descriptive statistic that had been done before. This study recommends that other researchers find and test the different types of empowerment. The management should evaluate employee idea scheme and use the feedback from the workforce to improve the organizational environment and fulfil their needs and skills. Employee empowerment practices should be reinforced by management in the district development authorities training as this will enable employees to effectively perform their responsibilities